Mental Anxieties, Bereavement, and Communication with the Dead Amongst Australian-Born. Issue 3 (2nd July 2016) - Ata, Abe W.
ABSTRACT: This article is based on survey of 269 households in the state of Victoria, Australia; 62 household of these are Australian born of a Christian background. This investigation tackles a much neglected, somewhat taboo and difficult area of family life and compares them with other religious and cultural groups: Significant differences were found with regards to health problems, grief expressions and practices, psychosomatic manifestations, communication with the dead, beliefs in the afterlife and interpretation of the meaning of loss. These findings offer a positive care-giving interventions and hopeful understanding of these issues in multicultural societies like ours.